2018
DOI: 10.22630/pniks.2018.27.2.22
|View full text |Cite
|
Sign up to set email alerts
|

Identyfikacja, oznaczanie oraz metody klasyfikowania gruntów organicznych w aspekcie Eurokodu 7 i norm związanych

Abstract: This paper draw attention to problems connected with recognize, classification, nomenclature and researches of organic soils according to Eurocode 7 and connected standards. Gather and put together current standard recommendation in the subject matter. Related to another guidelines and point on necessity to specify and supplement the recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Based on the analysis of the exploratory research carried out in the study area at the Rzeszów site, with the CPTM probe used at a maximum depth 15.4 m below ground level, frequently occurring and varied organic soils were identified in the subsoil. The test results show the values of the cone resistance qc and sleeve friction fs, in addition to the friction ratio Rf, which was used for the classification of the organic soil type using known criteria (p.2.1), as presented in the diagrams in Existing laboratory research has shown that, in the subsoil, a full spectrum of organic soils are present, from the low to high organic soil, which, due to ambiguous and simplified extant classification criteria [53,54], in comparison to the withdrawn national standard guidelines [55], is currently difficult to exactly define [56,57]. The organic content of the researched soils ranged from ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis of the exploratory research carried out in the study area at the Rzeszów site, with the CPTM probe used at a maximum depth 15.4 m below ground level, frequently occurring and varied organic soils were identified in the subsoil. The test results show the values of the cone resistance qc and sleeve friction fs, in addition to the friction ratio Rf, which was used for the classification of the organic soil type using known criteria (p.2.1), as presented in the diagrams in Existing laboratory research has shown that, in the subsoil, a full spectrum of organic soils are present, from the low to high organic soil, which, due to ambiguous and simplified extant classification criteria [53,54], in comparison to the withdrawn national standard guidelines [55], is currently difficult to exactly define [56,57]. The organic content of the researched soils ranged from ca.…”
Section: Resultsmentioning
confidence: 99%
“…The complete results of the index properties of organic soils at the study area at the Rzeszow site are summarized in Table 1. Existing laboratory research has shown that, in the subsoil, a full spectrum of organic soils are present, from the low to high organic soil, which, due to ambiguous and simplified extant classification criteria [53,54], in comparison to the withdrawn national standard guidelines [55], is currently difficult to exactly define [56,57]. The organic content of the researched soils ranged from ca.…”
Section: Resultsmentioning
confidence: 99%
“…Tests for determination of soil organic matter (SOM) in accordance of Polish Standard were carried out [8]. However, the identification of land based on organic matter content is not explicit because currently there are different classification systems in Poland, which the author pointed out in another paper [14]. Classification of soils containing organic matter according to the commonly used for engineering purposes of the Polish Standard [8] is distinguished by: humus soils (2<SOM<5%), warps, muds (5<SOM<30%) and peats (SOM>30%).…”
Section: Results Of Determinations and Testsmentioning
confidence: 99%
“…Generally these soils were wet and moisture peats mixed with organic muds (siOr, clOr), sandy silts (saSi) and medium sands (MSa) [12]. Acquiring samples of organic soils is very difficult and complicated, mainly due to the compressibility of the material and retention mainly below the ground water table [13,14], therefore samples for laboratory analyses in a new calibration chamber structure were collected with the disturbed, while drilling CFA piles.…”
Section: Characteristic Of the Study Areamentioning
confidence: 99%